Letter (copy) : re Mr. George Jeger - Morgan, H. B. (Hyacinth Bernard Wenceslaus Morgan), 1885-1956
1940-04-15 C02-0015-001 Telephone: Maida Vale 1384. Ref: EGG/ JMH. 4, Aberdare Gardens, Hampstead, London, N.W.6, 15th April, 1940. E.O. Gant. Esq., The Secretary, British Social Hygiene Council, Inc., Tavistock House South, Tavistock Square, LONDON, W.C.1. Dear Sir, re Mr. George Jeger. In reply to your letter of the 9th, I beg to give the above applicant for the post of Lecturer-Organiser as good and as favourable a recommendation as possible. He was my Organising-Secretary when I was Chairman of the Spanich Medical Aid Committee; a rather difficult Committee doing a very difficult job, and I can speak in the highest terms of the way in which he handled the whole of the organising and the collection of funds for that purpose. In addition I have know Mr. Jeger for many years, as he is the brother of my colleague Mr. S. Jeger, and there can be no doubt from his past experience and his ability that he is quite capable of doing the work which you have mentioned. He is sober, steady, has quite a sane moderate outlook, expresses himself with lucidity, and is in a position to deal with any problems that may arise in any position involving responsibility and trust. I think him eminently suitable for such a post and every reliance can be placed on him, his character, and his ability; his honesty is beyond challenge; his judgment is extremely good, and his behaviour always reliable. Yours truly, 292C/946/2/15(i)